Fabrication and characterization of a single-bridge nanorod between microgap electrodes. Issue 2 (29th April 2014) - Humayun, Qazi; Kashif, Muhammad; Hashim, Uda
Abstract : Purpose: – The purpose of this study was to investigate the performance of a single-bridge ZnO nanorod as a photodetector. Design/methodology/approach: – The fabrication of the design sensor with ∼6-μm gap Schottky contacts and bridging of the ZnO nanorod were based on conventional photolithography and wet-etching technique. Prior to bridging, the ZnO nanorods were grown by the hydrothermal process. The 0.35 M seed solution was prepared by dissolving zinc acetate dihydrate in 2-methoxyethanol, and monoethanolamine, which acts as a stabilizer, was added drop-wise. Before starting the solution deposition, and oxide, titanium (Ti) and gold (Au) layer deposition, p -type (100) silicon substrate was cleaned with Radio Corporation of America (RCA1) and RCA2, followed by dipping in diluted hydrofluoric acid. The aged solution was dropped onto the surface of the Au microgap structure, using a spin coater at a spinning speed of 3, 000 rpm for 45 seconds, and then dried at 300°C for 15 minutes, followed by annealing at 400°C for 1 hour. The hydrothermal growth was carried out in an aqueous solution of zinc nitrate hexahydrate (0.025 M) and hexamethyltetramine (0.025 M). Findings: – In this study, ZnO nanorods were grown on a SiO2 substrate by the hydrothermal method. Microgap electrodes with ∼6-μm spacing were achieved by using the wet-etching process. After the growth process, an area-selective mask was utilized to reduce the number of rods between the nearby gap areas. The obtained single ZnO nanorod was tested for the UV-sensing application. The single ZnO nanorod photodetector exhibited a UV photoresponse, thereby indicating potential as a cost-effective UV detector. The response and recovery times of the fabricated device were 65 and 95 seconds, respectively. Structural analysis was captured using X-ray Diffraction (XRD), whereas surface morphology was determined using scanning electron microscopy. Originality/value: – This paper demonstrates the effect of UV photon on a single-bridge ZnO nanorod between microgap electrodes.